Solid oxide battery and composition for air electrode thereof
By using ABO3 compounds in the air electrodes of solid oxide batteries, combining ion-electronic conductors and ionic conductors, the problems of easy damage to the battery under pressure and insufficient electrode conductors are solved, and performance improvements are achieved.
Patent Information
- Application Number
- CN202380053282.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-01-20
- Filing Date
- 2023-07-04
- Publication Date
- 2025-02-28
AI Technical Summary
Existing solid oxide batteries are susceptible to pressure during assembly and operation, and at the same time, the ion and electron conductivity of their electrode layers are insufficient, which affects performance.
A solid oxide cell with a novel structure is employed, wherein the air electrode comprises a compound represented by ABO3, A includes La, B includes at least one of Fe, Mn or Co, and Sc, and the content of Sc is less than 10 mol relative to the total content of 100 mol of B. The air electrode improves ion conductivity by combining ion-electronic conductors and ionic conductors.
By improving the ion conductivity of the air electrode, the overall performance of the solid oxide battery is improved and its performance as a fuel cell or a water electrolytic battery is enhanced.
Smart Images

Figure CN119547227A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a solid oxide cell and a composition for an air electrode of a solid oxide cell. Background Art
[0002] Solid oxide fuel cells (SOFC) and solid oxide electrolysis cells (SOEC) include cells composed of solid electrolytes with air electrodes, fuel electrodes and oxygen ion conductivity, and the cells may be referred to as solid oxide cells. Solid oxide cells generate electrical energy by electrochemical reactions, or electrolyze water by the reverse reaction of solid oxide fuel cells, thereby generating hydrogen. Compared with other types of fuel cells or water electrolysis cells (such as phosphoric acid fuel cells (PAFC), alkaline fuel cells (AFC), polymer electrolyte fuel cells (PEMFC), direct methanol fuel cells (DMFC)), solid oxide cells have low overvoltage based on low activation polarization, and have high efficiency due to low irreversible losses. In addition, because solid oxide cells can be used not only with hydrogen fuel, but also with carbon or hydrocarbon fuels, it can have a wide range of fuel selection, and because solid oxide cells have high reaction rates in electrodes, it does not require expensive precious metals as electrode catalysts.
[0003] In the actual implementation of devices such as fuel cells and water electrolysis cells, a stacking structure in which interconnectors and solid oxide cells are stacked on each other has been widely used. In the process of assembling the stacking structure of solid oxide cells or operating the device, pressure may be applied to the solid oxide cells, which may cause the solid oxide cells to rupture or be damaged.
[0004] The electrode layers of a solid oxide cell may include ionically and electronically conductive materials, and it is desirable to increase the overall conductivity of the electrode layers to improve the performance of the solid oxide cell. Summary of the invention
[0005] Technical issues
[0006] One aspect of the present disclosure is to realize a solid oxide cell with improved performance by including an electrode layer with high ionic conductivity in the solid oxide cell. In addition, another aspect of the present disclosure is to provide a composition for an air electrode of a high-efficiency solid oxide cell, which serves as an ion-electron conductor.
[0007] Solutions to the problem
[0008] In order to solve the above problems, according to one aspect of the present disclosure, a new type of solid oxide battery is proposed, which includes: a fuel electrode; an air electrode; and an electrolyte, which is arranged between the fuel electrode and the air electrode, wherein the air electrode includes an ion-electron conductor and an ion conductor, and the ion-electron conductor includes a 3 A compound represented by , wherein A includes La, and B includes at least one of Fe, Mn or Co and Sr.
[0009] According to some example embodiments of the present disclosure, A further includes at least one of Sr or Ca.
[0010] According to some example embodiments of the present disclosure, with respect to 100 mol of the total content of A, the content of at least one of Sr or Ca is less than or equal to 40 mol.
[0011] According to some example embodiments of the present disclosure, the content of Sc is less than 10 mol relative to 100 mol of the total content of B.
[0012] According to some example embodiments of the present disclosure, the content of Sc is greater than or equal to 5 mol relative to 100 mol of the total content of B.
[0013] According to some example embodiments of the present disclosure, the ion conductor includes at least one of scandia stabilized zirconia (SSZ), yttria stabilized zirconia (YSZ), scandia ceria stabilized zirconia (SCSZ), scandia ceria yttria stabilized zirconia (SCYSZ), or scandia ceria ytterbia stabilized zirconia (SCYbSZ).
[0014] According to some example embodiments of the present disclosure, a weight ratio of the ion-electron conductor to the ion conductor in the air electrode is 30:70 to 70:30.
[0015] In addition, according to another aspect of the present disclosure, a solid oxide cell includes: a fuel electrode; an air electrode; and an electrolyte disposed between the fuel electrode and the air electrode, wherein the air electrode includes an ion-electron conductor, the ion-electron conductor includes an ABO 3 A compound represented by: wherein A includes La, B includes at least one of Fe, Mn or Co and Sc, and the content of Sc is less than 10 mol relative to 100 mol of the total content of B.
[0016] According to some example embodiments of the present disclosure, the content of Sc is greater than or equal to 5 mol relative to 100 mol of the total content of B.
[0017] According to another aspect of the present disclosure, a composition for an air electrode of a solid oxide battery is provided, wherein the composition is composed of ABO 3 It means that A includes La, B includes at least one of Fe, Mn or Co and Sc, and the content of Sc is less than 10 mol relative to the total content of 100 mol of B.
[0018] According to some example embodiments of the present disclosure, the content of Sc is greater than or equal to 5 mol relative to 100 mol of the total content of B.
[0019] Advantageous Effects of the Invention
[0020] When a solid oxide cell is implemented using the composition for an air electrode of a solid oxide cell according to some exemplary embodiments of the present disclosure, the ion conductivity of the air electrode can be improved. When such a solid oxide cell is used as a fuel cell or a water electrolysis cell, its performance can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is a cross-sectional view schematically illustrating a solid oxide cell according to some example embodiments of the present disclosure;
[0022] Figure 2 is a cross-sectional view schematically showing a solid oxide battery according to another example embodiment of the present disclosure;
[0023] Figure 3 Yes Figure 1 An enlarged view of a region of the fuel electrode (i.e., region R1) is shown;
[0024] Figure 4 Yes Figure 1 An enlarged view of a region of the air electrode (i.e., region R2) is shown;
[0025] Figure 5 is a graph showing the results of measuring the change in conductivity with temperature in air electrodes obtained by compositions having different Sc addition amounts;
[0026] Figure 6 is a graph showing measurement of polarization resistance of oxygen reduction reaction in air electrodes obtained by compositions having different Sc addition amounts;
[0027] Figure 7 It shows H 2 - A diagram showing the results of TPR (temperature programmed reduction) analysis;
[0028] Figure 8is a graph showing the relationship between current density and voltage in a solid oxide cell including an air electrode obtained by a composition having different Sc addition amounts and power density according to them; and
[0029] Fig. 9 is a graph showing the relationship between current density and voltage in an air electrode formed by mixing a composite obtained by mixing LSFScO5 (Sc: 5 mol%) and an ion conductor (YSZ), and power density according to them. DETAILED DESCRIPTION
[0030] Hereinafter, the example embodiments of the present disclosure will be described with reference to specific example embodiments and the accompanying drawings. However, the example embodiments of the present disclosure may be illustrated in many different forms and should not be construed as being limited to the specific embodiments set forth herein. The example embodiments disclosed herein are provided to enable those skilled in the art to better explain the present disclosure. In the accompanying drawings, for the sake of clarity, the shapes and sizes of the elements may be exaggerated, and the same reference numerals will always be used to represent the same or similar elements.
[0031] In order to clearly explain the present disclosure in the drawings, contents irrelevant to the description are omitted, the thickness of each component is magnified to clearly indicate multiple layers and regions, and components having the same functions within the scope of the same concept are described using the same reference numerals. Throughout the specification, unless otherwise specified, when a part "includes" or "contains" a component, this indicates that other components are not excluded and other components may be further included.
[0032] Unless expressly stated otherwise, the phrase "at least one of..." means any combination of one or more of those items. For example, unless specifically stated otherwise, "at least one of X, Y, or Z" may be only X, only Y, only Z, or any combination thereof (e.g., X, Y, and / or Z).
[0033] Figure 1 is a cross-sectional view schematically illustrating a solid oxide cell according to some example embodiments of the present disclosure. Figure 2 is a cross-sectional view schematically illustrating a solid oxide cell according to another example embodiment of the present disclosure. Figure 3 is an enlarged view of a region of the fuel electrode (ie, region R1), and Figure 4 is an enlarged view of the region of the air electrode (ie, region R2).
[0034] Reference Figures 1 to 4The solid oxide cell 100 according to some example embodiments of the present disclosure includes a fuel electrode 110, an air electrode 120, and an electrolyte 130 as main components, and the electrolyte 130 is disposed between the fuel electrode 110 and the air electrode 120. Here, the air electrode 120 includes an ion-electron conductor 121 and an ion conductor 122. In addition, the ion-electron conductor 121 includes a 3 A compound represented by wherein A includes La, and B includes at least one of Fe, Mn or Co and Sc. In the example embodiment, since the air electrode 120 includes the ion-electron conductor 121 having high ionic conductivity, the reactivity in the air electrode 120 can be improved, thereby improving the performance of the solid oxide cell 100. Hereinafter, the components of the solid oxide cell 100 are described in detail, and the case where the solid oxide cell 100 is used as a fuel cell is mainly described. However, the solid oxide cell 100 can also be used as a water electrolysis cell, and in this case, the opposite reaction to the case of the fuel cell will occur in the fuel electrode 110 and the air electrode 120 of the solid oxide cell 120.
[0035] The fuel electrode 110 and the air electrode 120 correspond to electrode layers where a main reaction occurs in the solid oxide cell 100. Specifically, when the solid oxide cell 100 is a fuel cell, for example, an oxidation reaction of generating water or a carbon compound by oxidation of hydrogen may occur in the fuel electrode 110, and an oxygen ion generation reaction due to oxygen decomposition may occur in the air electrode 120. When the solid oxide cell 100 is a water electrolysis cell, a reaction opposite to the above reaction may occur, for example, hydrogen may be generated according to a reduction reaction of water in the fuel electrode 110, and oxygen may be generated in the air electrode 120. In addition, as another example, when the solid oxide cell 100 is a fuel cell, a hydrogen decomposition (hydrogen ion generation) reaction occurs in the fuel electrode 110, and oxygen and hydrogen ions may be combined to generate water in the air electrode 120, and when the solid oxide cell 100 is a water electrolysis cell, a water decomposition (hydrogen and oxygen ion generation) reaction may occur in the fuel electrode 110, and oxygen may be generated in the air electrode 120.
[0036] In addition, Figure 1In the case of the solid oxide cell 100, the fuel electrode 110 and the air electrode 120 may correspond to the so-called electrolyte 130 supported solid oxide cell 100 supported by the electrolyte 130, and in this case, the width of the electrolyte 130 may be the widest and / or thickest among the fuel electrode 110, the air electrode 120 and the electrolyte 130. The electrolyte 130 supported solid oxide cell 100 may have excellent reliability, and the electrolyte 130 may be formed relatively thick to perform a supporting function. However, in addition to the electrolyte 130 supported type, other structures may be adopted. For example, as Figure 2 As shown in the example embodiment of , the solid oxide cell 100 may be implemented as a fuel electrode 110 supported type, and in this case, the fuel electrode 110 may be the widest and / or thickest among the fuel electrode 110, the air electrode 120, and the electrolyte.
[0037] like Figure 3 As shown in FIG. 1 , the fuel electrode 110 may include an electronic conductor 111 and an ion conductor 112, and the fuel electrode 110 may be a sintered body of particles. The electronic conductor 111 may perform an electrical conduction function and a catalyst function, and may include, for example, a Ni-based material, a lanthanum chromate-based material (La 1-x Sr x CrO 3 , where 0≤x<1). In addition, the electron conductor 111 may include yttria-stabilized zirconia-based (YSZ) materials, ceria-based (CeO 2 ) materials, bismuth oxide-based (Bi 2 O 3 ) materials and / or lanthanum gallate-based (LaGaO 3 ) material. In addition, the fuel electrode 110 may be a porous body including pores H1, and gas, fluid, etc. may enter and leave through the pores H1.
[0038] The electrolyte 130 may be provided between the fuel electrode 110 and the air electrode 120, and ions may move to the fuel electrode 110 or the air electrode 120. As an example of a material constituting the electrolyte 130, materials constituting the ion conductors 112 and 122 of the fuel electrode 110 and the air electrode 120, respectively, may be used. As a representative example, the electrolyte 130 may include stabilized zirconia. Specifically, the electrolyte 130 may include scandia stabilized zirconia (SSZ), yttria stabilized zirconia (YSZ), scandia ceria stabilized zirconia (SCSZ), scandia ceria yttria stabilized zirconia (SCYSZ), and / or scandia ceria ytterbia stabilized zirconia (SCYbSZ).
[0039] like Figure 4 As shown in FIG. 1 , the air electrode 120 may include an ion-electron conductor 121 and an ion conductor 122, and the air electrode 120 may be a sintered body of particles. The air electrode 120 may be a porous body including pores H2, and gas, fluid, etc. may enter and leave through the pores H2. As described above, the ion-electron conductor 121 may include an ion conductor 122 made of ABO. 3 A compound represented by , wherein A may include La, and B may be obtained from a composition for an air electrode including at least one of Fe, Mn or Co and Sc, and Sc may improve the ion conductivity of the air electrode 120. In addition, when a composite material of the ion-electron conductor 121 is used instead of using only an electron conductor, the interface between the ion conductor and the electron conductor may be increased, which may increase the effective reaction area in the air electrode 120. La-based oxides (such as La 0.8 Sr 0.2 MnO 3 ) is close to an electronic conductor having low ionic conductivity, and when a La-based oxide is used, the reaction region may be limited to an interface between the air electrode 120 and the electrolyte 130 or an interface between an electronic conductor and an ionic conductor in the air electrode 120. In this example embodiment, the ion-electron conductor 121 having a composition in which Sc is partially substituted at the site B may be used to enhance the reactivity of the air electrode 120.
[0040] On the other hand, the ion conductor 122 may include at least one of scandia stabilized zirconia (SSZ), yttria stabilized zirconia (YSZ), scandia ceria stabilized zirconia (SCSZ), scandia ceria yttria stabilized zirconia (SCYSZ), or scandia ceria ytterbium stabilized zirconia (SCYbSZ). By including the ion conductor 122, the ion conductivity can be further improved in the air electrode 120, and the reaction area can be increased. The weight ratio of the ion-electron conductor 121 to the ion conductor 122 in the air electrode 120 may be in the range of 30:70 to 70:30. When the weight ratio of the ion-electron conductor 121 in the air electrode 120 is reduced to less than 30%, the electron conduction path may not be sufficiently ensured. In addition, when the weight ratio of the ion conductor 122 is reduced to less than 30%, the three-phase interface that can be set as the reaction zone in the air electrode 120 may not be sufficiently ensured.
[0041] However, in the case of using the ion-electron conductor 121 in which the site B is partially substituted with Sc as in the present example embodiment, the air electrode 120 may have high ion conductivity, and in this case, the air electrode 120 may not include the ion conductor 122 .
[0042] Specifically describing the composition of the ion-electron conductor 121, the ion-electron conductor 121 basically has the formula ABO 3 The perovskite structure represented by , wherein A is a lanthanum-based oxide including La. In the present disclosure, A may also include at least one of Sr or Ca. That is, since at least one of Sr or Ca may be added to the composition of the ion-electron conductor 121, a portion of La may be replaced by at least one of Sr and Ca in site A. In the present disclosure, the content of Sr or Ca, or the total content of Sr and Ca, relative to 100 mol of the total content of A, may be less than or equal to 40 mol (40 mol%). In some embodiments, the content of Sr or Ca may be greater than 0 mol (0 mol%) relative to 100 mol of the total content of A.
[0043] B includes at least one of Fe, Mn and Co and Sc. In other words, in addition to polyacid elements such as Fe, Mn and Co, Sc is added to the composition of the ion-electron conductor 121, that is, it is doped with Sc, and some polyacid elements are replaced by Sc. Sc has a fixed oxidation number (+3), and it should be understood that oxygen vacancies can be induced by replacing some polyacid elements (such as Fe, Mn and Co), thereby improving ionic conductivity. In this case, considering characteristics such as electrical conductivity and ionic conductivity, the content of Sc can be set to a more appropriate range. Specifically, the content of Sc in the ion-electron conductor 121 may be less than 10 mol (10 mol%), less than 9 mol (9 mol%), less than 8 mol (8 mol%), less than 7 mol (7 mol%) or less than 6 mol (6 mol%), relative to the total content of 100 mol of B, and more specifically, the content of Sc in the ion-electron conductor 121 may be greater than or equal to 5 mol (5 mol%), greater than or equal to 6 mol (6 mol%), greater than or equal to 7 mol (7 mol%), greater than or equal to 8 mol (8 mol%), or greater than or equal to 9 mol (9 mol%), relative to the total content of 100 mol of B.
[0044] In some embodiments, the ion-electron conductor may include (La (1-a-b) Sr a Ca b )(B' (1-x) Sr x ) 3 The ion-electron conductor 121 may include LaFeO 3 、LaScO 3 、LaMnO 3 、LaCoO 3 、SrFeO 3 , SrScO 3 、SrMnO 3 、SrCoO 3 、CaFeO 3 , CaScO 3 、CaMnO 3 or CaCoO 3 .
[0045] The inventors measured various characteristics by manufacturing an air electrode 121 using a composition having the above-mentioned composition conditions, and compared the measured characteristics with a comparative example (no Sc added). In addition, the characteristics were examined by dividing the conditions into the case where the ion-electron conductor 121 to which Sc was added was used alone and the case where the ion conductor 122 was used together with Sc.
[0046] first, Figure 5 is a graph showing the results of measuring the change in conductivity with temperature in air electrodes obtained by compositions having different Sc addition amounts. Here, LSF (Sc: 0 mol%) means La 0.6 Sr 0.4 FeO 3 , LSFSc05(Sc:5mol%) represents La 0.6 Sr 0.4 Fe 0.95 Sc 0.05 O 3 , LSFSc10(Sc:10mol%) represents La 0.6 Sr 0.4 Fe 0.9 Sc 0.1 O 3 , and LSFSc20(Sc:20mol%) represents La 0.6 Sr 0.4 Fe 0.8 Sc 0.2 O 3 . Reference Figure 5 The experimental results show that when Sc is added to the LSF composition, the conductivity is lower than that of the LSF composition. It can be seen that as the amount of Sc added increases, the conductivity decreases. Therefore, it can be understood that when Sc with a fixed oxidation number is added to the ABO 3 When the perovskite structure is represented by site B, the Zener double-exchange mechanism can reduce the conductivity. However, according to the research of the present inventors, it can be found that even if the conductivity is slightly reduced by adding Sc, there is no problem in the function as the air electrode 120, and compared with this, as described below, the effect of improving the performance by increasing the ion conductivity is significant.
[0047] then, Figure 6 : is a graph showing the measurement of polarization resistance of oxygen reduction reaction in air electrodes obtained by compositions having different Sc addition amounts. Figure 6In the graph of , the horizontal axis represents the real part of impedance, and the vertical axis represents the imaginary part of impedance, and half of the distance between the two X-intercepts in each curve corresponds to the polarization resistance. Referring to the experimental results, it can be seen that, compared with the LSF composition, except for LSFSc20 (Sc: 20mol%), when Sc is added, the polarization resistance tends to decrease. It can be understood that although Sc is added to reduce conductivity, the polarization resistance of the electrode may be relatively reduced due to the increase in the oxygen vacancy concentration in the material to improve the overall oxygen ion conductivity. In checking Figure 7 H 2 -The results of the temperature programmed reduction (TPR) analysis showed that the amount of Sc was related to the amount of Fe 3+ ions are formed at lower temperatures, from which it can be predicted that oxygen vacancies are more easily formed. In addition, when the polarization resistance of the electrode is measured according to the oxygen partial pressure, it can be inferred where the reaction determination step of the corresponding electrode is, and therefore, it can be known that when the reaction rate determination value (i.e., the m value) is closer to 1, the gas diffusion step is the reaction rate determination step. Table 1 below shows the reaction rate determination value (i.e., the m value) according to the amount of Sc added and the temperature, from which it can be seen that with the increase in the amount of Sc added, the m value (calcined at 1050°C) increases. In addition, the m value increases rapidly in the composite electrode mixed with 50wt% of the pure ion conductor YSZ, from which it can be confirmed that the effect of adding Sc is basically the same as that of the mixed ion conductor.
[0048] [Table 1]
[0049]
[0050] then, Figure 8 : is a graph showing the relationship between current density and voltage in a solid oxide cell including an air electrode obtained by a composition having different Sc addition amounts and power density according to them. Figure 8 As shown in the graph of , among the multiple lines, a substantially straight line represents voltage (i.e., left vertical axis), and a parabola represents power density (i.e., right vertical axis), where power density corresponds to the product of current density and voltage. Referring to the experimental results, it can be seen that the air electrode including the ion-electron conductor having a composition in which Sc is added in an amount of 5 mol% has the highest output power density.
[0051] then, Fig. 9 : is a diagram showing the relationship between current density and voltage in an air electrode formed by mixing a composite obtained by mixing LSFScO5 (Sc: 5 mol%) and an ion conductor (YSZ). Here, the weight ratio of the ion-electron conductor included in the composite to the ion conductor is 1. Fig. 9 As can be seen from the experimental results of , it can be found that when an ion conductor is added in addition to the ion-electron conductor, the power is increased by 30% or more. In addition, as described in the experimental results of Table 1, when an ion conductor such as YSZ is added, a rapid reaction order improvement result similar to that of adding Sc can be obtained. The weight ratio of LSFSc05 to YSZ in this example may not be limited and may be in the range of 30:70 to 70:30.
[0052] The present disclosure is not limited to the above-mentioned exemplary embodiments and the accompanying drawings, but is limited by the appended claims. Therefore, those of ordinary skill in the art may make various substitutions, modifications or changes without departing from the scope of the present disclosure defined by the appended claims, and these substitutions, modifications or changes should be interpreted as being included within the scope of the present disclosure.
Claims
1. A solid oxide battery comprising: Fuel electrode; Air electrode; as well as an electrolyte disposed between the fuel electrode and the air electrode, wherein the air electrode comprises an ion-electron conductor and an ion conductor, and The ion-electron conductor includes a compound represented by ABO3, wherein A includes La, and B includes at least one of Fe, Mn, or Co, and Sr.
2. The solid oxide battery according to claim 1, wherein: A also includes at least one of Sr and Ca.
3. The solid oxide battery according to claim 2, wherein: The content of at least one of Sr and Ca is less than or equal to 40 mol relative to 100 mol of the total content of A.
4. The solid oxide battery according to claim 1, wherein: The content of Sc is less than 10 mol relative to 100 mol of the total content of B.
5. The solid oxide battery according to claim 4, wherein: The content of Sc is greater than or equal to 5 mol relative to 100 mol of the total content of B.
6. The solid oxide battery according to claim 1, wherein: The ion conductor includes at least one of scandia stabilized zirconia (SSZ), yttria stabilized zirconia (YSZ), scandia ceria stabilized zirconia (SCSZ), scandia ceria yttria stabilized zirconia (SCYSZ) and / or scandia ceria ytterbia stabilized zirconia (SCYbSZ).
7. The solid oxide battery according to claim 1, wherein: The weight ratio of the ion-electron conductor to the ion conductor in the air electrode is 30:70 to 70:
30.
8. A solid oxide battery comprising: Fuel electrode; Air electrode; as well as an electrolyte disposed between the fuel electrode and the air electrode, wherein the air electrode comprises an ion-electron conductor, The ion-electron conductor includes a compound represented by ABO3, wherein A includes La, B includes at least one of Fe, Mn or Co and Sc, and The content of Sc is less than 10 mol relative to 100 mol of the total content of B.
9. The solid oxide battery according to claim 8, wherein: The content of Sc is greater than or equal to 5 mol relative to 100 mol of the total content of B.
10. A composition for an air electrode of a solid oxide battery, wherein: The composition includes a compound represented by ABO3, wherein A includes La, B includes at least one of Fe, Mn or Co and Sc, and The content of Sc is less than 10 mol relative to 100 mol of the total content of B.
11. The composition for an air electrode of a solid oxide battery according to claim 10, wherein: The content of Sc is greater than or equal to 5 mol relative to 100 mol of the total content of B.
12. The composition for an air electrode of a solid oxide battery according to claim 10, wherein: A also includes Sr.
13. The composition for an air electrode of a solid oxide battery according to claim 10, wherein: The content of Sr is less than or equal to 40 mol relative to 100 mol of the total content of A.
14. The composition for an air electrode of a solid oxide battery according to claim 10, wherein: The content of Sc is less than 10 mol relative to 100 mol of the total content of B.
15. The composition for an air electrode of a solid oxide battery according to claim 10, wherein: B includes Sc and Fe.
16. The composition for an air electrode of a solid oxide battery according to claim 10, wherein: B includes Sc and Mn.
17. The composition for an air electrode of a solid oxide battery according to claim 10, wherein: B includes Sc and Co.
18. The solid oxide battery according to claim 1, wherein: A further comprises Sr, and the ion conductor comprises yttria-stabilized zirconia (YSZ).
19. The solid oxide battery according to claim 1, wherein: B includes Sr and Fe.
20. The solid oxide battery according to claim 19, wherein: The weight ratio of the compound represented by ABO3 to yttria-stabilized zirconia (YSZ) in the air electrode is 30:70 to 70:30.